Worsening child outcomes?: caregiver imprisonment and its impact on child poverty, health, well-being and education in Uganda - Butler, Michelle (European journal on criminal policy and research, 2021)
Increasingly, research investigates how the imprisonment of those with child care responsibilities may affect children and their outcomes. However, this research is often conducted in high-income, developed countries, with little known about its impact in low-income, least developed countries. This study starts to address this gap by examining if the imprisonment of those with child care responsibilities in Uganda, a low-income least developed country, may affect child poverty, wellbeing, health, diet, and education. Drawing on 76 interviews conducted with 61 adults and 15 children, participants were asked to recount what affect, if any, imprisonment of the child’s caregiver was believed to have on child poverty, health, wellbeing, diet, and education. The findings reveal that imprisonment was believed to have a largely negative effect on these aspects of children’s lives for most children, hindering government efforts to improve child outcomes and tackle key development challenges. Based on these findings, it is argued that our theoretical understanding of imprisonment and its effects may need to be broadened to include how differing socio-economic policy contexts may moderate the impact of imprisonment on child outcomes.